Gluing Performance of Mixed Hardwood Tabletop - Sutopo, Sry (1991)
In formation of gluing properties suitability on tropical wood species is lacking. This study was conducted to provide important information on the possible use of certain species and types of adhesives. Gluing performance of three hardwood species i.e. Kelempayan (Anthocephalus chinensis), Yellow meranti (Shorea spp.) and Rubberwood (Hevea brasiliensis) with Urea formaldehyde (UF) and Polyvinyl acetate (PVAc) was carried out. The differences between species as well as types of adhesives used showed a very significant effect on the gluing performance of the assembled material. Species combination glued with UF resulted in shear strength exceeded the minimum industrial requirements of 5.5 MPa and 4.1 MPa under dry and wet conditions respectively. Yellow meranti single species and Kelempayan-Rubberwood combination under wet condition did not meet the requirement. PVAc glued materials did not meet the minimum industrial requirement. Rubberwood-Rubberwood combinations glued with UF produced boards with highest shear strength of 10.8 MPa and average wood failure of 93.0 percent. Performance of mixed-species Rubberwood-Kelempayan comb ination glued with UF produced boards with highest shear strength of 9.4 MPa and the average wood fa1lure of 96.0 per cent. Generally, mixed- species combinations resulted in comparable strength properties with single species combination except that of Rubberwood glued with UFO Nevertheless, gluing performance of Rubberwood with PVAc improved when combined with Kelempayan or Yellow meranti. Surface quality of adherend had a major effect in gluing performance especially when PVAc adhesive was used. This means adherend with smoother surface produce worse gluing performance.